Th cytokine profile in childhood-onset systemic lupus erythematosus - Wei Quan; Jingnan An; Gang Li; Guanghui Qian; Meifang Jin; Chenxi Feng; Si Li; Xiaozhong Li; Yunyun Xu; Xiaohan Hu (BMC, 2021)
Abstract Background Childhood-onset systemic lupus erythematosus (cSLE) is a kind of chronic inflammatory disease characterized by a highly abnormal immune system. This study aimed to detect the serum levels of Th (T helper) cytokines (IL-2, IL-4, IL-5, IL-6, IL-9, IL-10, IL-13, IL-17A, IL-17F, IL-21, IL-22, IFN-γ and TNF-α) in cSLE and healthy controls, and then to elucidate their association with clinical manifestations, disease activity and laboratory parameters. In order to provide clues for early diagnosis and timely intervention treatment of cSLE patients. Methods A total of 33 children with cSLE and 30 healthy children were enrolled in this study. Children in the cSLE group were classified into the inactive or active cSLE group according to their SLE disease activity index 2000 (SLEDAI-2 K) score. Th cytokine profiles in the peripheral blood were detected and analysed. Results Levels of IL-2, IL-10 and IL-21 in the cSLE group were significantly higher than those in the healthy control group (P < 0.05, P < 0.01 and P < 0.01, respectively). Expression of IL-2, IL-10 and IL-21 in the active cSLE group was significantly higher than that in the healthy control group (P < 0.05, P < 0.01 and P < 0.05, respectively), but that of IL-22 expression was markedly lower in the active cSLE group than in the healthy control group (P < 0.001). IL-21 in the inactive SLE group was significantly higher than that in the healthy control group (P < 0.05), and levels of IL-2 and IL-10 in the active cSLE group were significantly higher than those in the inactive cSLE group (P < 0.01 and P < 0.05). In-depth analysis showed that after excluding age, gender and drug interference, the levels of IL-2 (P < 0.05), IL-6 (P < 0.05) and IL-10 (P < 0.05) were still positively correlated with SLEDAI-2 K scores. However, the levels of IL-6 (P < 0.05) and IFN- γ (P < 0.05) were still negatively correlated with CD4+/CD8+, and the concentration of IL-6 (P < 0.05) was still positively correlated with the occurrence of nephritis. Conclusion This study provides a theoretical basis for the discovery of effective methods to regulate imbalance in T lymphocyte subsets in cSLE, which may lead to new approaches for the diagnosis of cSLE.